The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s40571-022-00459-9
|View full text |Cite
|
Sign up to set email alerts
|

Application and benchmark of SPH for modeling the impact in thermal spraying

Abstract: The properties of a thermally sprayed coating, such as its durability or thermal conductivity depend on its microstructure, which is in turn directly related to the particle impact process. To simulate this process, we present a 3D smoothed particle hydrodynamics (SPH) model, which represents the molten droplet as an incompressible fluid, while a semi-implicit Enthalpy-Porosity method is applied for modeling the phase change during solidification. In addition, we present an implicit correction for SPH simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This includes having direct access to the neighborhood search needed for an efficient evaluation of the ray tracer. Additionally, since SPlisHSPlasH has already been used in the process simulations of tungsten inert gas welding (TIG) and thermal spraying, the temperature and fluid simulation can be leveraged for a full process simulation in future [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes having direct access to the neighborhood search needed for an efficient evaluation of the ray tracer. Additionally, since SPlisHSPlasH has already been used in the process simulations of tungsten inert gas welding (TIG) and thermal spraying, the temperature and fluid simulation can be leveraged for a full process simulation in future [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…For the subsequent process simulation, smoothed particle hydrodynamics has been shown to be well applicable to the simulations of heat and mass transfer needed in welding engineering [6][7][8][9][10][11]. Due to the meshless, Lagrangian nature of smoothed particle hydrodynamics, it conserves mass by construction and eases the treatment of topological changes.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the gridbased method induces expensive computational time and imprecision outcomes [17][18][19]. To resolve these issues, the particle-based Smoothed Particle Hydrodynamics (SPH) method has been employed to simulate the thermal spray process [20][21][22][23][24][25]. The SPH method is a mesh-free Lagrangian method for simulating fluid flows and natural phenomena that involve complex deformations, free surface flows, and moving particles.…”
Section: Smoothed Particle Hydrodynamics (Sph) Methodsmentioning
confidence: 99%
“…The SPH method is a mesh-free Lagrangian method for simulating fluid flows and natural phenomena that involve complex deformations, free surface flows, and moving particles. Because of its advantage, the SPH method has been applied to study various multiphase fluid problems [18,[20][21][22][23][24][25][39][40][41][42][43][44]. The SPH method was applied to investigate the effects of contact angle and surface tension on the outcome of the YSZ droplet impact [20]; they found that the impact angle is less than 44°, and the droplet splash occurred.…”
Section: Smoothed Particle Hydrodynamics (Sph) Methodsmentioning
confidence: 99%
See 1 more Smart Citation